Gestión de la experiencia del cliente como herramienta para la internacionalización de las instituciones de educación superior de Barranquilla (2020)
His research seeks to analyze customer experience management as a tool for the internationalization of Barranquilla's educational institutions, based on the theoretical approaches of Schmitt (2003); Pine & Gilmore (1998); Meyer & Schwager (2007); Gronholdt, Martensen, Jorgensen & Jensen (2015); Gentile, Spiller & Noci (2007); Konecnik & Gartner (2007); Hollbrook & Hirschmann (1982) in the client experience management variable and with the theoretical approaches Wit (1995) and Castillo, Bernuy and Lastres (2005) in the internationalization variable. With a deductive epistemological approach, a descriptive quantitative paradigm and a non-experimental field design, the survey technique was used and through a questionnaire with a Likert-type scale, the heads or directors of the units were approached as the population under study major internationalization of 13 Higher Education institutions active in the National Higher Education Information System. The data were collected and processed using descriptive statistics: means, relative and absolute frequencies, mean central tendency, mode, median and standard deviation. With the multiple linear regression model, a mathematical function was identified that deduced that the customer experience process I represent had the highest contribution with 91.5%. The study confirmed that Customer Experience Management solves the problem of the insertion of Barranquilla's higher education institutions in educational spaces in international contexts when customer experience strategies, customer experience processes and the design of the service.